Incidence of decision to delivery interval delay in emergency LSCS and its impact on fetal and maternal outcome: a prospective observational study - Singh, Priya T.; Salana, Karishma; Nehate, Meetali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Caesarean delivery is a complex multidisciplinary procedure. Decision to delivery interval is supposed to play a significant role in maternal and neonatal outcomes. The present study was undertaken to determine the incidence of DDI delay among pregnant women undergoing Emergency LSCS in tertiary care centres. Methods: This study was conducted on 400 subjects who underwent emergency LSCS in category I and category II during a period from November 2020 to August 2021. Results: The maximum patients were from the age group of 25-29 years (43%), primigravida (59.1%), gestational age between 37-40 weeks (78%). 29% have undergone category-1 LCSC and 71.2% have undergone category-2 LSCS. Out of 116 patients underwent category-1 LSCS, 11 (9.5%) patient delay was present whereas in category-2 LSCS out of 284,12 (4.2%) patient delay was present. Among Category-I LSCS the most common indication was Fetal distress and among Category-II LSCS the major indication was non reassuring CTG. Maximum babies have APGAR scores between 7-10 at 1 (N=369) and 5 min (N=398). The mean cord PH was 7.31, ranged from 6.9-7.47. 98 babies required NICU admission and most of them admitted for respiratory distress. 11 patients required blood transfusion. There was no significant association found between various parameters and DDI delay, (p>0.05). Conclusions: In the present study, the interval between the decision to delivery interval has no significant impact on feto-maternal outcome in Category-I LSCS. Among Category-II LSCS there was a delay in 12 cases, among them 7 babies required NICU admission, the complications among neonates were significantly more when DDI was >75 minutes.